Effects of thickness and amount of carbon nanofiber coated carbon fiber on improving the mechanical properties of nanocomposites - Ghaemi, Ferial; Ahmadian, Ali; Yunus, Robiah; Ismail, Fudziah; Rahmanian, Saeed (MDPI, 2016)
In the current study, carbon nanofibers (CNFs) were grown on a carbon fiber (CF) surface by using the chemical vapor deposition method (CVD) and the influences of some parameters of the CVD method on improving the mechanical properties of a polypropylene (PP) composite were investigated. To obtain an optimum surface area, thickness, and yield of the CNFs, the parameters of the chemical vapor deposition (CVD) method, such as catalyst concentration, reaction temperature, reaction time, and hydrocarbon flow rate, were optimized. It was observed that the optimal surface area, thickness, and yield of the CNFs caused more adhesion of the fibers with the PP matrix, which enhanced the composite properties. Besides this, the effectiveness of reinforcement of fillers was fitted with a mathematical model obtaining good agreement between the experimental result and the theoretical prediction. By applying scanning electronic microscope (SEM), transmission electron microscope (TEM), and Raman spectroscopy, the surface morphology and structural information of the resultant CF-CNF were analyzed. Additionally, SEM images and a mechanical test of the composite with a proper layer of CNFs on the CF revealed not only a compactness effect but also the thickness and surface area roles of the CNF layers in improving the mechanical properties of the composites.